اثر استخدام تمرینات خاصة لسرعة مھارة السھم لتطویر سرعة الأداء والاتزان ودقة الإصابة - عامر فاخر شغاتي; صباح نوري حاف (الرياضة المعاصرة, 2016)
Section one Research Problem : most of duel players suffer from inability to maintain the same level of arrow motor skill during opponent attack due to weakness of performance speed and special maintain hence to weaker hit accuracy. The two aims of the research : 1- set a special trainings for arrow skill speed on population sample . 2- identify the impact of these trainings to develop performance speed ,stability and hit accuracy . Research filed : • Human filed : students of physical education college and sport sciences in annual 2014-2015. • Temporality filed : the duration from 12/2/2015 until 14/4/2015. • Locative filed : fencing hall / physical of education college and sport sciences. section two :theoretical studies that concerning this research. section three : include the methodology with empirical aspect , the research sample is students of physical education college and sports sciences and divides into two groups (empirical and adjusting) in (8) students for each group. section Four: include the display , analyze and discuss the results. Section five: Conclusions: Performs the work style and training method using arrow speed skills assists to develop rush performance , stability and hit accuracy . More development and impact has shown for empirical group than adjusting group . Recommendations: Necessity to use special trainings and exercises in arrow skill speed with workout on performance speed ,stability and hit accuracy. Perform researches and other studies according to physical and physiological variables for both genders and other sport activities